A construção da imagem literária curitibana entre os séculos XIX/XX: espelho e lente das tendências estéticas francesas - Siqueira, Vanderlei de (2020)
This study addresses the cultural and literary appropriations idealized by the writers from Paraná who contributed to the construction of an imagined identity, in the last decades of the 19th century and the beginning of the 20th century, as a representative of an artenovist behavior that shone in the Belle Époque of Curitiba. In our case, the objective is to suggest that, under the inspiration of French literature, local production gave new meaning to the concepts of modernity and urbanity through themes that dealt with the transitory and ephemeral in the urban space that was configured in the province recently elevated to state. . The focus of this dissertation’s approach is the analysis and interpretation of poems that, anchored in the dialogue with French writers, such as Baudelaire, Rimbaud, Mallarmé and Paul Verlaine, placed readers in the new historical moment. From the Symbolism and the literary production of the first two decades of the 20th century, there was a certain consolidation of an intellectualized thought about Paraná and, mainly, about Curitiba, which resulted in the need to define or affirm the local artistic identity. The theoretical foundation contemplates the hypotheses formed by Stanley Fish on the formation of interpretive communities, as well as Benedict Anderson’s ideas on imagined and socially constructed communities by common interests. In this sense, the present study organizes poems by Emiliano Perneta, Dario Vellozo, Silveira Neto and Rodrigo Junior in thematic sections that reveal the writing and the style of urban life, symbol of the cultural repertoire of Paraná.